Footballing backwater? A study of early Norfolk football. (2nd January 2023) - Curry, Graham
ABSTRACT: This article documents the early development of football, primarily the association game, in the county of Norfolk, England. Occasionally, the narrative extends to neighbouring counties, particularly Suffolk, its southern neighbour, to illustrate certain points of interest, but begins with an examination of 'camp-ball', an often violent folk football game played in Eastern England. Furthermore, the text represents another in a series of investigations into the game's beginnings with the long-term aim of throwing more light on local variations in how football was diffused into the wider society. In modern football's landscape, Norfolk is not regarded as a hotbed of the game, but, largely because of the profile of 'camp-ball' as a well-regarded and enthusiastically supported pursuit, one might think that football would have thrived swiftly in its more modern forms.